(untitled) (Global Journals of Research in Engineering, 2023)
The physical properties of agricultural objects affected by moisture are essential for effective postharvest unit operations Raw peanut in India is used in a wide variety of forms and the process involved often soaking in water before being used as an ingredient in the preparation of different delicacies Soaking and grinding in preparation of seasonings are commonly used to garnish the most traditional fermented foods such as idly dosa vada and uttapam with several other breakfast items in the Indian subcontinent The effect of moisture content 6 57 to 35 07 on physical properties and the temperature 5 to 350C dependent soaking behavior of peanut kernel of GG-20 genotype were assessed The increase in moisture content of peanuts has affected the dimensional characteristics linearly whereas most of the gravimetric and frictional properties followed a nonlinear trend The feasibility of different models describing the hydration behavior was assessed for the peanut kernel The adequacy of fitted models was determined using the coefficient of determination R2 chi-square 2 and root mean square error RMSE The values of these parameters as higher R2 0 96 and lower 2 0 005 and RMSE 0 020 reflect the applicability of models in describing the soaking behavior of the peanut kernel The rate of moisture uptake at different temperatures during hydration depicts the process as diffusion-controlled in the primary phase with a higher absorption rate followed by a slower absorption rate during the secondary phase of hydration Effective diffusivity in the endothermic process of moisture absorption varied from 2 905 10-10 to 10 754 10-10 m2 sec over the studied temperature range with the activation energy of 32 175 KJ mol